Identification of Chemical Science Literacy Skills of Madrasah Aliyah Students in the Environmental Science Competency Aspect - Ikmalia, Helwa; Irwandi, Dedi; Bahriah, Evi Sapinatul (Jurnal Pendidikan Sains Universitas Muhammadiyah Semarang, 2026)
Scientific literacy, particularly environmental science competency, is essential for enabling students to understand and respond to contemporary environmental challenges. However, research on chemical science literacy in Islamic senior high schools (madrasah), especially in suburban regions, remains scarce — particularly studies linking the Fundamental Laws of Chemistry to the PISA 2025 environmental science competency framework. This study aimed to identify the level of chemical science literacy of 578 students from State Islamic Senior High Schools in Bogor Regency using a quantitative descriptive survey. Data were collected through a 40-item science literacy test based on the PISA 2025 framework, assessing three indicators: explaining human interactions with Earth systems, evidence-based environmental decision making, and respecting diverse perspectives in socio- ecological crises. Results showed students achieved a high overall level of chemical science literacy. The highest achievement was explaining human interactions with Earth systems, while evidence-based decision-making was the lowest. These findings imply that chemistry teachers should integrate inquiry-based and socio-scientific strategies into instruction, and that curriculum developers should embed PISA-oriented environmental tasks to strengthen students' scientific decision-making competency.